Chromosome Painting in Cultivated Bananas and Their Wild Relatives (Musa spp.) Reveals Differences in Chromosome Structure - Šimoníková, Denisa; Němečková, Alžběta; Čížková, Jana; Brown, Allan; Swennen, Rony; Doležel, Jaroslav; Hřibová, Eva (International journal of molecular sciences, 2020)
Edible banana cultivars are diploid, triploid, or tetraploid hybrids, which originated by natural cross hybridization between subspecies of diploid Musa acuminata, or between M. acuminata and diploid Musa balbisiana. The participation of two other wild diploid species Musa schizocarpa and Musa textilis was also indicated by molecular studies. The fusion of gametes with structurally different chromosome sets may give rise to progenies with structural chromosome heterozygosity and reduced fertility due to aberrant chromosome pairing and unbalanced chromosome segregation. Only a few translocations have been classified on the genomic level so far, and a comprehensive molecular cytogenetic characterization of cultivars and species of the family Musaceae is still lacking. Fluorescence in situ hybridization (FISH) with chromosome-arm-specific oligo painting probes was used for comparative karyotype analysis in a set of wild Musa species and edible banana clones. The results revealed large differences in chromosome structure, discriminating individual accessions. These results permitted the identification of putative progenitors of cultivated clones and clarified the genomic constitution and evolution of aneuploid banana clones, which seem to be common among the polyploid banana accessions. New insights into the chromosome organization and structural chromosome changes will be a valuable asset in breeding programs, particularly in the selection of appropriate parents for cross hybridization.
Keywords: malování chromozomů; Plant Breeding; Crops, Agricultural; karyotype evolution; Chromosome Painting; structural chromosome heterozygosity; triploidie; zemědělské plodiny; šlechtění rostlin; chromosome translocation; molekulární evoluce; karyotyp; translokace genetická; Evolution, Molecular; chromozomy rostlin; Chromosomes, Plant; Musa; oligo painting FISH; fluorescence in situ hybridization; tetraploidie; Diploidy; Translocation, Genetic; banánovník; Tetraploidy; Triploidy; diploidie; Karyotype